Healthcare Marketing in the Digital Era: Performance Measurement and Experiential Value in a Maternal and Child Hospital in Indonesia - Mujtahidah, Mujtahidah; Samsiana, Samsiana; Jeki Purnomo (Journal of Scientific Insights, 2026)
Healthcare marketing in the digital era is increasingly shaped by data‑driven performance measurement and patient‑centered experiential value, particularly in specialized settings such as maternal and child hospitals. This study examines how a private maternal and child hospital—RSIA Ananda Makassar—implements digital marketing within a value‑based framework, focusing on its integration with performance measurement systems and experiential value creation for women and families. The research adopts a qualitative case study design using structured observation, semi‑structured interviews with key marketing and clinical staff, and documentation analysis of digital content, service processes, and patient feedback mechanisms over a two‑month period. Data were analyzed thematically to identify patterns in digital engagement, performance indicators, and experiential value dimensions. The findings reveal that Instagram, online booking, and WhatsApp‑based consultation are the most effective digital channels in reaching young mothers, while QR‑based satisfaction surveys and routine performance reviews support continuous improvement of marketing and service strategies. Patient trust and emotional bonding are strengthened through care‑oriented communication, storytelling, and visible professionalism, reflecting experiential value in maternal and childcare. However, global outreach and systematic integration of performance data across units remain limited. The study concludes that successful digital healthcare marketing in a maternal and child hospital requires an integrated approach that aligns digital tools, robust performance measurement, and patient‑centered experiential value to build trust and loyalty.